2001
DOI: 10.1007/s002160101071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of natural nanophases on heavy-metal retention in zeolite-supported reactive filtration facilities for urban run-off treatment

Abstract: The retention of lead in zeolite-supported sand-filter columns has been tested with focus on the effect of potentially mobile natural nanophases (natural colloids, humic substances). It could be shown that interaction of lead with natural nanophases enhanced the mobility of the contaminant. In the presence of iron oxide particles (goethite) a normal breakthrough of lead was observed. Humic substance can act as a carrier for lead itself and can enhance the mobility of lead bound to inorganic nanophases, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Because of their importance for environmental processes, natural iron oxide colloids and IONM have been investigated intensively (Banfield and Zhang, 2001). Due to their relatively straightforward synthesis (although receiving a certain property in a reproducible way can become an art) and widely available synthesis protocols (Schwertman and Cornell, 2000) they have been used as model colloids/NMs to understand aggregation processes (Hunter et al, 1997;Mylon et al, 2004;Baalousha et al, 2008) and colloidal/nanoparticulate transport Grolimund et al, 1998;Kuhnen et al, 2000) and contaminant cotransport in freshwaters, soil porewaters (Von der Kammer et al, 2004), and groundwaters (Forstner et al, 2001).…”
Section: Emissions and Main Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their importance for environmental processes, natural iron oxide colloids and IONM have been investigated intensively (Banfield and Zhang, 2001). Due to their relatively straightforward synthesis (although receiving a certain property in a reproducible way can become an art) and widely available synthesis protocols (Schwertman and Cornell, 2000) they have been used as model colloids/NMs to understand aggregation processes (Hunter et al, 1997;Mylon et al, 2004;Baalousha et al, 2008) and colloidal/nanoparticulate transport Grolimund et al, 1998;Kuhnen et al, 2000) and contaminant cotransport in freshwaters, soil porewaters (Von der Kammer et al, 2004), and groundwaters (Forstner et al, 2001).…”
Section: Emissions and Main Characteristicsmentioning
confidence: 99%
“…Their stabilization against aggregation by adsorption of NOM is well studied Forstner et al, 2001). However, the interaction with polysaccharides (e.g., in waste water treatment plants) will lead to immediate aggregation and removal .…”
Section: Aggregation and Stabilizationmentioning
confidence: 99%
“…Past studies have identified that while the colloidal and clay-size (<2 lm) fractions of particles may constitute a small gravimetric percentage of the gradation on a mass basis, these entrained particles can be of significant importance with respect to transport and bioavailability of metals and organic compounds (Forstner et al, 2001;Goldberg, 1991, 1993;Yuan et al, 2001). In the aqueous environment, clay particles are surface active and react with metal species and organics due to high specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that iron oxide colloids with negatively charged surface coatings are very mobile in quartz sand (Foerstner et al ., ; Tosco et al ., ; Carstens et al ., ). Our results show that their mobility is strongly reduced where iron oxide coats the solid matrix (Experiments 1.1 and 2.1; Figures ; Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%